PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN CANVA UNTUK MENINGKATKAN SEMANGAT PESERTA DIDIK PADA MATERI IPAS KELAS V - Cahyani, Yulia Fajar Dwi; Fatayan, Arum; Amaliyah, Nurrohmatul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop interactive learning media assisted by Canva on the water cycle material for fifth grade elementary school students. The results of the initial analysis showed that the previous learning process was not optimal, especially in the use of interesting and effective learning media. For this reason, the development of Canva-assisted media was carried out with the ADDIE approach, which includes the stages of analysis, design, development, implementation, and evaluation. The resulting media is designed to meet the criteria of validity, practicality, and effectiveness in order to improve the enthusiasm and learning outcomes of students. The results of the study showed that this media has a very high level of validity with a percentage of 95%, which is included in the